Reconfigurable sub-6 GHz 5G user-terminal MIMO antenna integrated with ISM 2.4 GHz band. (27th October 2022) - Lad, Varsharani Madhukar; Kulhalli, Kshama Vishwanath; Kumar, Jayendra
In this paper, a two-element, the two-mode reconfigurable multiple-input-multiple-output antenna is reported. The antenna is designed for the 5G 3.5 GHz and ISM 2.45 GHz integrated services. The antenna radiators are meander line-inspired and investigated for different configurations onboard to ensure self-isolation. The switching is realised using a single pin diode-based active circuit. The prototype of the antenna exhibits good impedance matching better than -10 dB, a reasonable gain of 1.2 dBi in ISM 2.4 GHz and 1.8 dBi in 3.5 5G bands and co and cross-polarisation isolation of above -15 dB. The optimised position and orientation of the two antenna elements exhibit excellent self-isolation of 27.6 dB ensuring better MIMO performance parameters with better coverage. The matching between simulation and measurement results are appreciable.